LEARNING ENVIRONMENTS AND THE USE OF VOCABULARY LEARNING STRATEGIES: A CASE STUDY OF CHINESE LEARNERS - Wang Dakun; Simon Gieve (Indonesian JELT, 2008)
This paper reports a survey study of how Chinese students use strategies when learning second language vocabulary. The focus of the study is on the effect of learning environments (EFL vs. ESL) on the use of vocabulary learning strategies. The subjects are Chinese secondary school students learning English in China (EFL context) and in Singapore (ESL context).The questionnaire used in the survey was a modified version of Gu and Johnson (1996). 450 secondary school students, aged from 16 to 19, from two secondary schools in Harbin, China, and one boarding school in Singapore participated in the survey. The profile of the students’ learning beliefs, sources and strategies was examined in relation to their learning environments. The t-test results showed that learning environment was significant factors in affecting vocabulary learning beliefs, sources and strategy use. The findings suggest that language environments can influence individuals’ vocabulary learning profile. Thus, the combined effects of the teaching emphasis and the amount of exposure to the target language in and out of the classroom should be considered closely in order to understand the strategy choice of Chinese EFL and ESL learners.　Key words:  Vocabulary learning strategies; Context, environment; EFL; ESL